Aqueous dispersions of organogel nanoparticles – potential systems for cosmetic and dermo‐cosmetic applications. (16th May 2014) - Kirilov, P.; Rum, S.; Gilbert, E.; Roussel, L.; Salmon, D.; Abdayem, R.; Serre, C.; Villa, C.; Haftek, M.; Falson, F.; Pirot, F.
Synopsis Objective The preparation and physicochemical characterization of organogel nanoparticles dispersed in water have been developed. These systems could be employed as nanocarrier for cosmetic applications or as hydrophobic reservoirs for drug delivery. Methods Gelled particles of organic liquid and 12‐hydroxystearic acid (organogelator) were obtained by hot emulsification (T>Tgel), with a surfactant (acetylated glycol stearate) and polymers (sodium hyaluronate and polyvinyl alcohol) as stabilizing agents, and cooling at room temperature (T<Tgel). An organic UVB sunscreen molecule, obtained by microwave activation, was used as a hydrophobic model molecule. The physicochemical properties of the starting organogel (gelation tests; rheological study) and the dispersed gelled particles (rheological study; particle mean size, size distribution, zeta‐potential measurements; physical stability evaluation; UVB absorption and water resistance ability) were studied. The synthesis of sunscreen compound using microwave activation was also described. Results According to the gelation test results, organogels were obtained with various organic liquids. Vaseline and almond oils were selected as organic medium for the gelled nanoparticle preparation. A preliminary formulation study was carried out in order to determine the optimal experimental conditions to obtain stable nanoparticle dispersions. Gelled nanoparticles contained the sunscreen model molecule, with mean size of 450 nm, polydispersity index of 0.18 and zeta‐potential value above −30 mV, were obtained by ultrasound probe homogenization method. A comparative study of their dispersion ageing showed a greatly enhanced stability after gelation. According to the UVB absorption evaluation, gelled particles improved the photoprotective ability and the photostability of immobilized UVB blocker. They showed a high water resistance ( 83%) even after 40 min of immersion. Conclusion The obtained results demonstrate the interest of these gelled nanoparticles and their aqueous dispersion for the preparation of new formulations for cosmetic and dermo‐cosmetic applications.